Preparation and characterization of polymeric micelles from uracil-containing amphiphilic copolymer for donepezil delivery - Erkent A.; Igdeli G.; YANIKOĞLU R. S.; TEMEL B. (My University, 2025)
Alzheimer\"s disease (AD) remains one of the most challenging neurodegenerative disorders, and the development of advanced drug delivery systems is critical to improve the therapeutic potential of existing treatments. In this study, uracil functionalized amphiphilic block copolymers were designed and synthesized via RAFT polymerization to prepare polymeric micelles as nanocarriers for donepezil (DNP) delivery. The successful synthesis of the monomer and copolymer was confirmed by spectroscopic and chromatographic techniques. The self-assembled micelles exhibited uniform nanoscale sizes, spherical morphology, and high thermodynamic stability due to uracil-mediated hydrogen bonding within the core. DNP was successfully encapsulated into the micelles, and in vitro release studies revealed a sustained and controlled drug release profile. Biological evaluations demonstrated that drug-loaded micelles preserved the acetylcholinesterase (AChE) inhibitory activity of DNP while reducing the inherent cytotoxicity observed in the free drug and empty micelles. These results highlight the potential of uracil-containing polymeric micelles as a promising nanocarrier platform for DNP delivery, offering improved stability, favorable release behavior, and enhanced biocompatibility, thereby contributing to the development of safer and more effective therapeutic strategies for AD.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Polimer Bilimi; Temel Bilimler (Sci); Polymer Science; Natural Sciences (Sci); Polimerler ve Plastikler; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Polymers and Plastics; Chemistry (miscellaneous); General Chemistry; Physical Sciences